Development of Monopoly-Based Learning Media for Strengthening School Norms Among Elementary School Students - Ahmad Husain; Nur Wahdaniyah; Glora Sri Handayani (Madako Elementary School, 2025)
The internalization of school norms is a crucial component in shaping character and discipline among primary school students. This study aims to strengthen the internalization of school norms among elementary students through the use of the Monopoly of Local Environment Rules media. The research was conducted using a Research and Development (R&D) approach within the ADDIE framework. A total of 30 second-grade students from SDN Kayu Putih 03 Jakarta participated as respondents to test the effectiveness of the media. Instrument validation results indicated a high level of feasibility, with scores of 90% from media experts, 89.41% from content experts, and 92% from language experts, all categorized as highly valid and suitable for use. Implementation of the media in learning elicited positive student responses, reflected in a total score of 1,135 out of a maximum of 1,200 (≈ 89.67%), classified as very attractive, and demonstrated increased student motivation and engagement in learning. The findings confirm that this media can enhance understanding and internalization of school norms while supporting the achievement of Pancasila Education learning objectives. The study’s implications suggest that the media can serve as an alternative, contextual, interactive, and enjoyable instructional strategy for instilling normative values in primary school students.